The very hungry Caterpillar : a very big board book - Carle, Eric (London : Puffin Books, 2011)
One sunny Sunday, the caterpillar was hatched out of a tiny egg. He was very hungry. On Monday, he ate through one apple; on Tuesday, he ate through three plums--and still he was hungry. Strikingly bold, colorful pictures and a simple text in large, clear type tell the story of a hungry little caterpillar's progress through an amazing variety and quantity of foods. Full at last, he made a cocoon around himself and went to sleep, to wake up a few weeks later wonderfully transformed into a butterfly!Brilliantly innovative designer and artist Eric Carle has dramatized the story of one of Nature's commonest yet loveliest marvels, the metamorphosis of the butterfly, in a picture book to delight as well as instruct the very youngest reader or listener. Cleverly die-cut pages show what the caterpillar ate on successive days, graphically introducing sets of up to 10 objects and also the names of the days of the week in rotation, as well as telling the central story of the transformation of the caterpillar. The final, double-page picture of the butterfly is a joyous explosion of color, a vibrant affirmation of the wonder and beauty of Nature. With its lovely, humorous illustrations and wonderful narrative about a hungry caterpillar growing up to be a beautiful butterfly, Eric Carle's story touches anyone who still has some growing to do. Along with reassuring repetition--"He was still hungry ..."--the book includes some wonderful interactive moments: what youngster can resist sticking a finger through that hole in the page as his ravenous friend makes his way through various delicacies?
Keywords: Caterpillar - fiction; Children - stories